2021
DOI: 10.1111/joes.12466
|View full text |Cite
|
Sign up to set email alerts
|

Is there a consensus on the health consequences of retirement? A literature review

Abstract: We investigate the causal effect of retirement on health through literature. We explore the potential mechanisms which explain three effects: the switch from employment to retirement, later retirement, and earlier retirement. The empirical strategies used to identify the causal effects are mainly based on the observation of changes in health status at the legal age for retirement entitlement or on reforms that have led to changes in retirement incentives. Literature renders possible to make several observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…A number of studies find positive effects of retirement on mental health (e.g., Atalay and 3 For a more detailed overview of the literature please refer to e.g. Garrouste and Perdrix (2021) Barrett, 2014; Atalay et al, 2019;Belloni et al, 2016;Charles, 2004;Eibich, 2015;Gorry et al, 2018;Grip et al, 2011;Leimer, 2017). Atalay and Barrett (2014), for example, exploit variation of a pension reform for women in Australia and find positive effects of retirement on mental health.…”
Section: Survey Data: Mental Healthmentioning
confidence: 99%
“…A number of studies find positive effects of retirement on mental health (e.g., Atalay and 3 For a more detailed overview of the literature please refer to e.g. Garrouste and Perdrix (2021) Barrett, 2014; Atalay et al, 2019;Belloni et al, 2016;Charles, 2004;Eibich, 2015;Gorry et al, 2018;Grip et al, 2011;Leimer, 2017). Atalay and Barrett (2014), for example, exploit variation of a pension reform for women in Australia and find positive effects of retirement on mental health.…”
Section: Survey Data: Mental Healthmentioning
confidence: 99%
“…In their quantitative analysis they find no evidence of a publication bias. Garrouste & Perdrix (2022) present a descriptive analysis of previous studies of which many find no effect of retirement on mental health, cognitive skills or mortality. They conclude that it is not always clear whether a non-significant effect is due to a lack of statistical power or an absence of effect.…”
Section: Overview Studiesmentioning
confidence: 99%
“…However, the cost and benefits of retirement on health and wellbeing has seen conflicting results [ 1 , 3 - 5 ]. Some reviews find that retirement decreases stress, improve health perceptions, and lower the severity of medical diseases [ 1 , 6 ]. Other studies however found that retirement increase social isolation [ 7 ], and even advocate the benefits of working beyond retirement [ 8 ].…”
Section: Introductionmentioning
confidence: 99%